Purely spatial diffusion of H atoms in solid normal- and para-hydrogen films - Sheludiakov S; Lee DM; Khmelenko VV; Dmitriev YA; Järvinen J; Ahokas J; Vasiliev S (AMER PHYSICAL SOC, 2022)
We present an experimental study of quantum diffusion of atomic hydrogen in solid H-2 films at temperatures below 1 K. The atoms are generated via electron impact dissociation by running a continuous rf discharge in helium gas above the H-2 film for long (up to 30 days) times. We are able to distinguish between the diffusion of the atoms moving towards each other followed by their recombination and the pure spatial diffusion driven by the density gradient. We found that in both cases the flux of phonons generated by the discharge above the surface of molecular film is essential to observe the slow diffusive motion. We obtained rates of pure spatial diffusion of H atoms in normal-H-2 (75% ortho, 25% para) films which were two orders of magnitude faster than those obtained from the H atom recombination, the quantity used in all previous work to characterize the mobility of H atoms in solid H-2. We investigated the influence of the film thickness and its ortho-para composition on recombination and pure spatial diffusion. For thin enough films of 0.16 mu m we observed complete diffusion of the H atoms through the entire film thickness. We observed peculiar behavior of the samples with ortho-H-2 (o-H-2) concentration below 5%. The recombination rate in these samples was an order of magnitude faster while the rate of spatial diffusion was somewhat slower than in films containing larger o-H-2 concentrations. The rate of production of H atoms in the low o-H-2 samples turned out to be an order of magnitude larger. We discuss possible explanations of these somewhat contradictory observations.